New frontiers in local government community engagement: Towards transformative place-based futures. (August 2021) - Osborne, Caroline; Mayo, Liam; Bussey, Marcus
Abstract: In the face of uncertainty and rapid change, how governments at all scales remain valued by society will depend on their ability to connect meaningfully, respond to challenges collaboratively, and co-design approaches with the community. However, tensions exist between the legislative obligations of local government organisations and meeting the rapidly growing needs of diverse communities, while simultaneously navigating the complexities of rapid change. Despite the efforts of local governments to obtain broad and representative input through community engagement processes, communities feel they have limited influence on decision-making processes. Further, Australian trust indices show declining levels of trust between the community, government and large institutions. So how can better community engagement practice be cultivated, evidenced, and continue to evolve to respond in increasingly complex contexts? Presenting a case study in the Sunshine Coast, Queensland, Australia, this article explores how a local government organisation is developing an innovative model of excellence in community engagement in collaboration with a regional university. Grounded in a place-based approach to community engagement, the innovation of this emerging model couples futures studies approaches to co-design locally appropriate responses to navigate increasing uncertainty and change. Drawing on literature from community engagement, participatory governance, futures studies and university-community partnerships, this article outlines a research agenda that explores how communities can strengthen their social and economic potential through place-based and futures thinking approaches.